2019
DOI: 10.1108/jmd-12-2018-0369
|View full text |Cite
|
Sign up to set email alerts
|

Competencies for effective public middle managers

Abstract: Purpose The purpose of this paper is to investigate a set of competencies that characterizes effective public middle managers. Design/methodology/approach A total of 20 middle managers from several public agencies were interviewed in person using the behavioral event interview technique. In all, 80 stories were deductively coded based on the existing National Civil Service Agency’s managerial competency dictionary and inductively examined through a thematic analysis to discover new themes. Findings This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 82 publications
0
23
0
5
Order By: Relevance
“…The OECD (2017) discusses insurgency, that is, challenging the status quo and working with common partners. In turn, Sudirman et al (2019), comment on the new skills for public managers that must be obtained by induction from a thematic analysis, such as adherence to laws, regulations, and collaborative attitudes. Although, entrepreneurs are seen as people prone to breaking rules, self-promotion and taking unjustified risks, while advocates see them as exercising leadership and simulating astuteness in initiatives.…”
Section: The Presentation Of Entrepreneurship Education Guidelines Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The OECD (2017) discusses insurgency, that is, challenging the status quo and working with common partners. In turn, Sudirman et al (2019), comment on the new skills for public managers that must be obtained by induction from a thematic analysis, such as adherence to laws, regulations, and collaborative attitudes. Although, entrepreneurs are seen as people prone to breaking rules, self-promotion and taking unjustified risks, while advocates see them as exercising leadership and simulating astuteness in initiatives.…”
Section: The Presentation Of Entrepreneurship Education Guidelines Inmentioning
confidence: 99%
“…In this scenario, providing excellent public services leads to reflection on the modeling of service provision of the public actor (Mattson & Anderson, 2019) as well as the morale of the civil servant (Gomes, Consoni & Lapolli, 2015). Thus, it is observed that governments are trying to create public value through emerging, disruptive, and intelligent technologies and strategies (Sudirman, Siswanto, Monang, & Aisha, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…How might circulation managers continue to contribute toward the whole of the library? The literature continues to document the pivotal roles middle managers play as change agents (Buick et al , 2018; Conway and Monks, 2011; Currie, 2000; Harding et al , 2014; Sudirman et al , 2019). Responding to change involves ever-changing institutional, professional and personal implications for professional practice, support from formal and informal networks, and continual training.…”
Section: Why So Admirable?mentioning
confidence: 99%
“…There are no empirical data, playbooks, crystal balls, forecasts or prognostications on the future of libraries as it relates to the complex role(s) of middle managers and those currently serving in circulation departments. Although, there is help for library middle managers to be effective when developing essential skills (Aho and Bennett, 2011), establishing positive roles (Chang and Bright, 2012; Patillo, 2018), initiating training (Rooney, 2010), facing challenges (Miller, 2020), building necessary skills and traits (Buller, 2018), competencies (Sudirman et al , 2019), negotiating influence (Laning and Nixon, 2013), building strategy (Floyd and Wooldridge, 2000; Rouleau and Balogun, 2011), fostering team building (Tinline and Cooper, 2016) and learning to stay on top (Madden et al , 2018). LaGuardia (2012) put it best when she observed that effective middle managers “Revel in the successes of their team/department/library, both the collective and individuals.”…”
Section: Why So Admirable?mentioning
confidence: 99%
“…A research paper by Sudirman et al (2019) focuses on identifying the competencies that are characteristic of effective middle managers. Data was gathered in personal interviews, using the behavioral event interview technique, from the responses of 20 middle manages working for several public agencies in West Java Province, Indonesia.…”
mentioning
confidence: 99%